2005
DOI: 10.1002/eji.200425547
|View full text |Cite
|
Sign up to set email alerts
|

Papillomavirus virus‐like particles induce cytokines characteristic of innate immune responses in plasmacytoid dendritic cells

Abstract: Human papillomavirus (HPV) virus-like particles (VLP) are being extensively tested as vaccines for the prevention of HPV-associated cervical cancer. Dendritic cells (DC) acquire and present antigens, initiating innate and adaptive immune responses. It has been shown previously that DC of the myeloid lineage are capable of generating adaptive immune responses to HPV VLP in vitro. However, the capacity of plasmacytoid DC (pDC) to acquire HPV VLP and the nature of the immune response generated have not been repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 44 publications
(67 reference statements)
0
33
0
1
Order By: Relevance
“…The apparent discordance of these results could be due to a different optimal timing for the sample collection and needs to be evaluated by more extensive observations. Nevertheless, the production of IFN-␥ by DCs induced with enveloped or nonenveloped VLP produced in different expression systems (prokaryotic, yeast, and baculovirus) is still a debated issue (18,28,30,49,53,54). In particular, Yang et al (53), reported that the CD8␣ ϩ…”
Section: Discussionmentioning
confidence: 99%
“…The apparent discordance of these results could be due to a different optimal timing for the sample collection and needs to be evaluated by more extensive observations. Nevertheless, the production of IFN-␥ by DCs induced with enveloped or nonenveloped VLP produced in different expression systems (prokaryotic, yeast, and baculovirus) is still a debated issue (18,28,30,49,53,54). In particular, Yang et al (53), reported that the CD8␣ ϩ…”
Section: Discussionmentioning
confidence: 99%
“…HPV L1 VLPs have been reported elsewhere to induce cytokine response in DCs, monocytes, and macrophages (41)(42)(43), possibly in a TLR-dependent fashion (44,45). Abs against HPV L1 VLPs were found to be reduced in TLR4-deficient mice by Yang et al (44) but not by others (46).…”
Section: Crucial Role Of Mpl In As04 For the Stimulation Of An Innatementioning
confidence: 96%
“…The results are also in agreement with the suspected role of pDCs in viral infections. Lenz and colleagues (21) showed in an in vitro study that HPV-16 is bound by freshly isolated immature pDCs and CpG maturated pDCs, that internalization of the virus preferentially occurs in immature pDCs, and that it induces the production of IFN-a and IL-6, important factors for the production of antibodies. Bontkes and colleagues (22) showed that pDCs are present in cervical cancer lesions and that HPV-16 virus-like particles are able to activate pDCs.…”
Section: Interestingly Mulvany and Allen (19) Observed Increased Nummentioning
confidence: 99%